2010
DOI: 10.1542/peds.2008-2248
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs of Adolescents and Parents Regarding Adolescent Suicide

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Suicide is the third leading cause of death for adolescents in the United States. Suicide prevention efforts often involve environmental modification, such as limiting access to lethal methods, and education, such as recognizing individual risk factors. WHAT THIS STUDY ADDS:This study examines the perceptions of adolescents and their parents regarding the risk, predictability, and preventability of teen suicide and explores what participants think about how to prevent suicide. abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 14 publications
0
29
0
5
Order By: Relevance
“…Parents will need information on how and where to obtain mental healthcare for their adolescents. They will also need information on the causes of mental health problems and issues regarding the stigma by some toward mental illness [39][40][41]. • Schools need to develop school-community partnerships specifically as ready sources of referral of students who threaten or have attempted suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Parents will need information on how and where to obtain mental healthcare for their adolescents. They will also need information on the causes of mental health problems and issues regarding the stigma by some toward mental illness [39][40][41]. • Schools need to develop school-community partnerships specifically as ready sources of referral of students who threaten or have attempted suicide.…”
Section: Discussionmentioning
confidence: 99%
“…It is the third most common cause of adolescent's death in USA. 19 In this study, the incidence of suicidal poisoning was much lower than that in Western countries. The reason for this is not known but might be because of the presence of strong religious sanctions against the suicide in Islam, the religion practiced by the majority of our population.…”
Section: Discussionmentioning
confidence: 51%
“…This theme relates to current research detailing that many children with depression and suicidal ideation are not identified 12 and that screening efforts can detect mental health conditions in children with nonpsychiatric complaints. 13,14 Focus group discussions with community adolescents and parents also suggest that parents do not believe that they are able to identify a suicidal adolescent, 15 which led the authors to conclude that systematic screening may be indicated. Overall, these responses suggest that youth who experience suicidal ideation may not volunteer this information unless specifically asked.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in parent-adolescent focus group discussions around the country, participants identified suicide as a nationwide concern but did not believe that adolescent suicide was a problem in their own communities. 15 …”
Section: Discussionmentioning
confidence: 99%